White matter and gray matter changes related to cognition in community populations - Li, Wen-Xin; Yuan, Jing; Han, Fei; Zhou, Li-Xin; Ni, Jun; Yao, Ming; Zhang, Shu-Yang; Jin, Zheng-Yu; Cui, Li-Ying; Zhai, Fei-Fei; Zhu, Yi-Cheng (Frontiers in Aging Neuroscience, 2023)
Objective Further studies are needed to improve the understanding of the pathological process underlying cognitive impairments. The purpose of this study is to investigate the global and topographic changes of white matter integrity and cortical structure related to cognitive impairments in a community-based population. Methods A cross-sectional analysis was performed based on 995 subjects (aged 56.8±9.1 years, 34.8% males) from the Shunyi study, a community-dwelling cohort. Cognitive status was accessed by a series of neurocognitive tests including Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), category Verbal Fluency Test (VFT), Digit Span Test (DST), and Trail Making Tests A and B (TMT-A and TMT-B). Structural and diffusional MRI data were acquired. White matter integrity was assessed using fractional anisotropy (FA), mean diffusivity (MD), and peak width of skeletonized mean diffusivity (PSMD). Cortical surface area, thickness, and volume were measured using Freesurfer. Probabilistic tractography was further conducted to track the white matter fibers connecting to the cortical regions related to cognition. General linear models were used to investigate the association between brain structure and cognition. Results Global mean FA and MD were significantly associated with performances in VFT (FA, β 0.119, p<0.001; MD, β -0.128, p<0.001). Global cortical surface area, thickness, and volume were not related to cognitive scores. In tract-based spatial statistics analysis, disruptive white matter integrity was related to cognition impairment, mainly in visuomotor processing speed and executive function (TMT-A and VFT), rather than short-term memory (DST). In the whole brain vertex-wise analysis, surface area in the left orbitofrontal cortex, right posterior-dorsal part of the cingulate gyrus, and left central sulcus were positively associated with MMSE and MoCA scores, and the association were independent of the connecting white matter tract. Conclusions Disrupted white matter integrity and regional cortical surface area were related to cognition in community-dwelling populations. The associations of cortical surface area and cognition were independent of the connecting white matter tract.